Penggunaan E-Money, Intensitas Jumlah Uang Beredar, dan Laju Inflasi di Indonesia - Asriatun Nafiah; Aulia, Darlin (Politeknik Negeri Ambon, 2022)
The increasing use of e-money in Indonesia is one of the government's goals in creating a cashless society environment. This study aims to determine how the influence of the use of e-money with the inflation rate in Indonesia which is mediated by the money supply. This study uses a quantitative approach with monthly secondary data for the years 2009-2021. The total sample used is 624 months. This study uses a general sample so that it does not focus on an e-money product. The data analysis technique used is descriptive statistics, while hypothesis testing is done through multiple linear regression analysis. The regression results in the first equation show that there is no significant effect of the volume of e-money transactions on inflation, but there is a significant negative effect of the value of e-money transactions on inflation. The regression results in the second equation show a positive and significant effect between the use of e-money both in terms of value and transaction volume proxies on the money supply. The regression results in the third equation show that there is no significant effect between the volume and value of e-money transactions with inflation mediated by the money supply.